A comprehensive overview of geopolymer composites: A bibliometric analysis and literature review. (June 2022) - Yang, Haihua; Liu, Liang; Yang, Wu; Liu, Hanlong; Ahmad, Waqas; Ahmad, Ayaz; Aslam, Fahid; Joyklad, Panuwat
Abstract: Cement is the main component of concrete, a widely used building material. Cement production requires substantial energy, exhausts natural resources, and causes CO2 emissions. Efforts are being undertaken to develop a concrete binder instead of cement. Geopolymer composite (GPC) is developed as a potential new building material, offering a clean alternative for construction sustainability. This study accumulated extensive bibliometric data on GPC from the Scopus database and conducted a scientometric analysis employing an appropriate software. The leading sources of publications, highly used keywords in the published articles, writers and papers with the highest citations, and active regions were all identified in the scientometric analysis. Manual reviews are unable to deal with the vast bibliometric data effectively. Additionally, this study covers the most crucial research concerns and shortcomings in existing research about GPC adoption and application. Lastly, further research guidelines are suggested. The scientometric review will assist academics from various states to exchange innovative ideas and expertize, encourage collaborative research, and develop joint ventures.